Schooling as Investment: The Need for a Poststructuralist Perspective in Educational Research in the Philippines - Fontejon-Bonior, Gina A. (Silliman Journal, 2022)
This paper argues for a poststructuralist perspective in studying the complex dynamics of schooling in socio-economically disadvantaged communities in the Philippines. It presents the limitations of interpreting learning in relation to learners' motivation particularly in the context where access to the language of power, English, plays a significant role in schooling. It then suggests that a more robust interpretation of schooling may be achieved by considering learning as apprenticeship to secondary Discourses. Schooling is not only an investment that allows for upward socio-economic mobility; it is also an experience of the construction of identity that positions learners in stances of power and enables them to counter hegemonic practices that further marginalize them. The paper attempts to justify the need for such perspective in research to inform educational reforms in the Philippines and raises questions that need to be addressed in such studies.